The relaxant effect of the extract of Crocus sativus petal on Wistar rats airway smooth muscle and its possible mechanisms - Sepide Behrouz; Arghavan Memarzia; Mohammad Hossein Eshaghi Ghalibaf; Amir Hossein Yazdi; Mohammad Hossein Boskabady (Avicenna Journal of Phytomedicine)
Objective: Obstructive pulmonary diseases are characterized by airflow limitation secondary to airway wall thickening, airway narrowing and increased mucus secretion. Saffron (Crocus sativus L.) has shown different effects including anti-inflammatory, antioxidant, and immunomodulatory properties and promising effects for treating multiple disorders. In this study, the contribution of calcium and potassium channels, muscarinic and histamine (H1) receptors in the relaxant effect of the C. sativus petal extract on tracheal smooth muscle (TSM) was assessed.Materials and Methods: Fifty-four male Wistar rats divided in 8 groups, were studied. TSM was contracted by 10 μM methacholine or 60 mM KCl for 5 min, and the relaxant effects of cumulative concentrations of C. sativus petal extract (0.1, 0.2, 0.4 and 0.8 mg/ml), theophylline (0.2, 0.4, 0.6 and 0.8 mM) or 1 mL normal saline were tested. In non-incubated TSM and in TSM groups incubated with diltiazem, chlorpheniramine, propranolol, glibenclamide, atropine and indomethacin, the relaxant effects of the extract were evaluated.Results: The concentration-dependent relaxant effects of C. sativus petal extract on non-incubated TSM contracted by methacholine or KCl, were observed (for all, p<0.001). The relaxant effects of C. sativus petal extract in TSM incubated with chlorpheniramine and indomethacin, were significantly reduced compared to non-incubated tissues (p<0.05 to p<0.001).Conclusion: The results showed an obvious relaxation effect of the petal of C. sativus extract on TSM and suggest that inhibition of cyclooxygenase pathway and histamine receptors contribute to the extract relaxant effect of the extract.